Finite Difference Approximation for Pricing the American Lookback Option (Journal of Computational Mathematics, 2009)
In this paper we are concerned with the pricing of lookback options with American type constrains. Based on the differential linear complementary formula associated with the pricing problem, an implicit difference scheme is constructed and analyzed. We show that there exists a unique difference solution which is unconditionally stable. Using the notion of viscosity solutions, we also prove that the finite difference solution converges uniformly to the viscosity solution of the continuous problem. Furthermore, by means of the variational inequality analysis method, the $\mathcal{O}(Δt+Δx^2)$-order error estimate is derived in the discrete $L_2$-norm provided that the continuous problem is sufficiently regular. In addition, a numerical example is provided to illustrate the theoretical results.
Keywords: American lookback options; Finite difference approximation; Stability and convergence; Error estimates.